The Role of Structured Mentoring Programs in Shaping Professional Competence Among Preservice Teachers: Evidence from a Quasi-Experimental Study - Muhammad Nur Akbar Rasyid; Syamsul Bahri (Journal of Innovation in English Education and Language Teaching, 2025)
Despite widespread recognition of mentoring as critical to initial teacher education, the typical apprenticeship model observed in many school placements remains largely unstructured, yielding inconsistent learning outcomes. This study investigated the effects of a structured 12 week mentoring program on multiple dimensions of professional competence among preservice teachers using a quasi experimental design. Sixty preservice teachers were allocated to an experimental group (structured mentoring, n = 30) or a control group (conventional practicum supervision, n = 30). Professional competence was assessed before and after the intervention using an adapted Professional Competence Scale covering instructional planning, classroom management, assessment literacy, and reflective practice. An analysis of covariance was performed with baseline scores as the covariate. After the intervention, the structured mentoring group significantly outperformed the control group across all competence subscales, with the largest gains observed in instructional planning (F = 12.47, p < .001, ηp² = .18) and reflective practice (F = 9.85, p < .01, ηp² = .15). The overall between group effect was substantial (d = 0.86). Qualitative interview data revealed that structured protocols, cognitive modelling, and cycles of focused feedback were the key mechanisms driving these improvements. Structured mentoring that embeds explicit scaffolding, goal setting, and process oriented feedback significantly enhances preservice teachers’ professional learning. Teacher education programmes should move beyond unstructured placement supervision and adopt systematically designed mentoring protocols to bridge the persistent gap between theoretical preparation and classroom readiness.